2020
DOI: 10.1089/biores.2020.0010
|View full text |Cite
|
Sign up to set email alerts
|

An Alginate-Based Hydrogel with a High Angiogenic Capacity and a High Osteogenic Potential

Abstract: In bone tissue engineering, autologous cells are combined with osteoconductive scaffolds and implanted into bone defects. The major challenge is the lack of post-implantation vascular growth into biomaterial. The objective of the present study was to develop a new alginate-based hydrogel that enhances the regeneration of bone defects after surgery. The viability of human bone marrow-derived mesenchymal stem cells (BM-MSCs) or human endothelial cells (ECs) cultured alone or together on the hydrogel was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These microspheres exhibited favorable characteristics for the sustained release of VEGF. Previous studies have suggested that spherical aggregate networks with diameters between 100–400 μm are optimal for oxygen diffusion and species exchange [ 20 ]. Therefore, by optimizing the preparation conditions, we selected 350 μm calcium alginate microspheres with high uniformity for cell encapsulation in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These microspheres exhibited favorable characteristics for the sustained release of VEGF. Previous studies have suggested that spherical aggregate networks with diameters between 100–400 μm are optimal for oxygen diffusion and species exchange [ 20 ]. Therefore, by optimizing the preparation conditions, we selected 350 μm calcium alginate microspheres with high uniformity for cell encapsulation in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various materials used for microsphere preparation, natural polysaccharide sodium alginate has gained significant attention owing to its high porosity, permeability, minimal mass transfer limitation, and high water content, particularly in loading and targeting drug delivery [ 18 , 19 ]. Alginate-based microcapsules have been extensively utilized for cell encapsulation, culture, and expansion of various cell types such as neural cells, osteoblasts, chondrocytes, and myoblasts [ 20 , 21 ]. This can be attributed to the rich biocompatibility and facile cross-linking process of alginates.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, encapsulation techniques enable application, especially in chronic cardiovascular disease due to the delayed release of reparative and pro-angiogenic cells. Despite auspicious results, encapsulation as a strategy for cell therapy has mostly remained a preclinical concept thus far [ 40 , 41 , 42 , 43 , 44 ].…”
Section: Encapsulation Techniques For Cell Transplantsmentioning
confidence: 99%
“…These characteristics lead to the difference of their high-order structures, so polyM, polyG and their derivatives display different activities [ 3 ]. In medical fields, alginates with different arrangement and degree of polymerization (DP) have wide application prospects, including drug delivery and tissue engineering [ 4 , 5 , 6 ]. Alginate oligosaccharides (AOS) and their derivatives with different DPs are becoming popular due to their favorable biological activity and water solubility [ 1 ].…”
Section: Introductionmentioning
confidence: 99%